Fibrinolysis by Bile - King, Burnham J. (Thrombosis and Haemostasis, 1972)
Fibrinolytic activity is described in the bile of man and of several species of mammal. This activity can be precipitated from whole bile by ammonium sulphate, by acetone, and by a chlor of orm/methanol partition technique. It behaves as an anion at pH 7.4. Ammonium sulphate precipitated bile is caseinolytic, and fibrinolytic on a heated fibrin plate. It gives a peak of fibrinolytic activity on column chromatography with sephadex G50 at Kav = 0.3, suggesting a molecular weight of ± 15,000.